External validation of the PROGRESS-CTO complication risk scores: Individual patient data pooled analysis of 3 registries. (15th March 2023) - Simsek, Bahadir; Tajti, Peter; Carlino, Mauro; Ojeda, Soledad; Pan, Manuel; Rinfret, Stephane; Vemmou, Evangelia; Kostantinis, Spyridon; Nikolakopoulos, Ilias; Karacsonyi, Judit; Dens, Joseph A.; Agostoni, Pierfrancesco; et al.
Abstract: Background: Chronic total occlusion (CTO) percutaneous coronary intervention (PCI) is associated with a considerable risk of complications, and risk stratification is of utmost importance. Aims: To assess the clinical usefulness of the recently developed PROGRESS-CTO (NCT02061436 ) complication risk scores in an independent cohort. Methods: Individual patient data pooled analysis of 3 registries was performed. Results: Of the 4569 patients who underwent CTO PCI, 102 (2.2%) had major adverse cardiovascular events (MACE). Patients with MACE were older (69 ± 11 vs. 65 ± 10, p < 0.001), more likely to have a history of prior coronary artery bypass graft surgery, and unfavorable angiographic characteristics J-CTO score (2.4 ± 1.2 vs. 2.1 ± 1.3, p = 0.007), including blunt stump (59% vs. 49%, p = 0.047). Technical success was lower in patients with MACE (59% vs. 86%, p < 0.001). The area under the receiver operating characteristic curve of the PROGRESS-CTO complication risk models were as follows: MACE 0.72 (95% confidence interval [CI], 0.67–0.76), mortality 0.73 (95% CI, 0.61–0.85), and pericardiocentesis 0.69 (95% CI, 0.62–0.77) in the validation dataset. The observed complication rates increased with higher PROGRESS-CTO complication scores. The PROGRESS-CTO MACE score showed good calibration in this external cohort, with MACE rates similar to the original study: 0.7% (score 0–1), 1.5% (score 2), 2.2% (score 3), 3.8% (score 4), 4.9% (score 5), 5.8% (score 6–7). Conclusion: Given the good discriminative performance, calibration, and ease of calculation, the PROGRESS-CTO complication scores could help assess the risk of complications in patients undergoing CTO PCI. Highlights: We evaluated the PROGRESS-CTO complication risk scores in an individual patient data pooled analysis of 3 CTO PCI registries. The c-statistic of the models were 0.72, 0.73, and 0.69 for MACE, mortality, and pericardiocentesis, respectively. The use of the PROGRESS-CTO complication risk should be considered to facilitate risk-benefit assessment in CTO PCI.